O morador de rua da cidade de Uberlândia atendido pela Casa Santa Gemma: vivências e representações - Lima, Danielle Vieira (2015)
In this dissertation, I seek to understand how the homeless served by Casa Santa Gemma in the city of Uberlândia see themselves and how society sees them from the analysis of social representations present in people‟s discourses. From a fieldwork in this care home I observed homeless‟ view of himself and the society in which he belongs. I also observed the view of passers-byinSquare Tubal Vilela, a route point for people from various levels of education and social class, in which I sought - by opinion survey - the social representation of homeless people in the vision of a non-probability sample, random, of the passerby citizen. Through a theoretical discussion and observation in field work I show traces of reality of homeless in the city of Uberlândia, outlining the processes of exclusion, poverty and stigmatization that mark their experiences. I also present the municipal public policies directed to homeless people, which are insufficient to meet the social demand. I have the assumption that these social subjects are not on the streets by choice, but among other reasons, because of economic, social and personal factors, such as lack of work and money, rupture of family ties, physical and psychological diseases.